Intrathecal morphine is superior to intravenous PCA in patients undergoing minimally invasive cardiac surgery - Mukherjee, Chirojit; Koch, Eva; Banusch, Joergen; Scholz, Markus; Kaisers, Udo X.; Ender, Joerg (Annals of cardiac anaesthesia, 2012)
Aim of our study was to evaluate the beneficial effect of low dose intrathecal morphine on postoperative analgesia, over the use of intravenous patient controlled anesthesia (PCA), in patients undergoing fast track anesthesia during minimally invasive cardiac surgical procedures. A randomized controlled trial was undertaken after approval from local ethical committee. Written informed consent was obtained from 61 patients receiving mitral or tricuspid or both surgical valve repair in minimal invasive technique. Patients were assigned randomly to 2 groups. Group 1 received general anesthesia and intravenous patient controlled analgesia (PCA) pump with Piritramide (GA group). Group 2 received a single shot of intrathecal morphine (1.5 \textgreekmg/kg body weight) prior to the administration of general anesthesia (ITM group). Site of puncture was confined to lumbar (L1-2 or L2-3) intrathecal space. The amount of intravenous piritramide used in post anesthesia care unit (PACU) and the first postoperative day was defined as primary end point. Secondary end points included: time for tracheal extubation, pain and sedation scores in PACU upto third postoperative day. For statistical analysis Mann-Whitney-U Test and Fishers exact test (SPSS) were used. We found that the demand for intravenous opioids in PACU was significantly reduced in ITM group (P <0.001). Pain scores were significantly decreased in ITM group until second postoperative day (P <0.01). There was no time delay for tracheal extubation in ITM group, and sedation scores did not differ in either group. We conclude that low dose single shot intrathecal morphine provides adequate postoperative analgesia, reduces the intravenous opioid consumption during the early postoperative period and does not defer early extubation.